Bioactive molecular network-guided discovery of dihydro-β-agarofurans from the fruits of Celastrus orbiculatus. (November 2022) - Kim, Jun Gu; Le, Thi Phuong Linh; Han, Jae Sang; Cho, Yong Beom; Kwon, Haeun; Lee, Dongho; Lee, Mi Kyeong; Hwang, Bang Yeon
Abstract: A bioactive molecular networking strategy has been applied to discovery of bioactive constituents from the fruits of Celastrus orbiculatus Thunb., which showed significant inhibitory effects on the α-MSH-induced melanin production in B16F0 melanoma cells. In the obtained molecular network, the nodes with relatively high bioactive scores were prioritized for isolation; as a result, 12 undescribed dihydro-β-agarofuran sesquiterpenes together with 15 known compounds were isolated from MeOH extracts of the fruits of C. orbiculatus . Their structures were elucidated based on the interpretation of NMR, HRESIMS, ECD data, and single crystal X-ray diffraction. Among the obtained isolates, celastorbin A and (1 R, 2 S, 4 R, 5 S, 7 S, 8 S, 9 R, 10 S )-1, 2, 8-triacetoxy-9-cinnamoyloxydihydro- β -agarofuran, which possessed high bioactive scores in the molecular network, exhibited potent inhibitory effects on the α-MSH-induced melanin production in B16F0 cells with IC50 values of 4.1 and 2.0 μM, respectively. Graphical abstract: Twelve undescribed dihydro- β -agarofurans were isolated from Celastrus orbiculatus using a bioactive molecular networking strategy. Celastorbin A and (1 R, 2 S, 4 R, 5 S, 7 S, 8 S, 9 R, 10 S )-1, 2, 8-triacetoxy-9-cinnamoyloxydihydro- β -agarofuran, which possessed high bioactive scores in the molecular network, showed potent inhibitory effects on the α-MSH-induced melanin production. Image 1 Highlights: A bioactivity-based molecular networking was applied to search bioactive chemicals of Celastrus orbiculatus. Twelve undescribed dihydro- β -agarofurans were isolated by target-isolation. Their structures were determined by NMR, HRESIMS, ECD, and single crystal X-ray diffraction. All compounds were tested for their inhibitory effects on the α-MSH induced melanin production.